Pengaruh Digitalisasi, Religiusitas, dan Keterikatan Pegawai terhadap Kinerja Pegawai Bank Syariah di Kota Banda Aceh dengan Kepatuhan Syariah sebagai Variabel Moderator - Putri Zahirah; Muhammad Yasir Yusuf; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
This study aims to examine the impact of digitalization, religiosity, and employee attachment on employee performance, with sharia compliance positioned as a moderating variable. The sample consists of 400 employees from Islamic banks in Banda Aceh, selected using simple random sampling techniques and calculated through the Slovin formula. This research emphasizes the utilization of primary data obtained via questionnaire distribution, analyzed using the Moderated Regression Analysis (MRA) statistical model. Findings indicate that, individually, digitalization, religiosity, and attachment exert a significant positive influence on the performance of Islamic bank employees in Banda Aceh. As a moderating variable, sharia compliance also demonstrates a significant positive effect on employee performance. The interaction between digitalization and sharia compliance significantly enhances employee performance. Additionally, the interaction between religiosity and sharia compliance positively influences employee performance. Similarly, the interaction between employee attachment and sharia compliance also reveals a significant positive impact on performance.